2020
DOI: 10.3390/ijms21176268
|View full text |Cite
|
Sign up to set email alerts
|

Polar Infection of Echovirus-30 Causes Differential Barrier Affection and Gene Regulation at the Blood–Cerebrospinal Fluid Barrier

Abstract: Echovirus-30 (E-30) is responsible for the extensive global outbreaks of meningitis in children. To gain access to the central nervous system, E-30 first has to cross the epithelial blood–cerebrospinal fluid barrier. Several meningitis causing bacteria preferentially infect human choroid plexus papilloma (HIBCPP) cells in a polar fashion from the basolateral cell side. Here, we investigated the polar infection of HIBCPP cells with E-30. Both apical and basolateral infections caused a significant decrease in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Our previous results suggested that the optimal infection rates of HIBCPP cells with E-30 were obtained when the cells were challenged apically with a MOI (multiplicity of infection) of 20 [ 28 ]. Now, we further analyzed several parameters, such as the transepithelial resistance, the cytotoxic effect of E-30, the number of viral particles per HIBCPP cells, and the percentage of infected HIBCPP cells ( Supplemental Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous results suggested that the optimal infection rates of HIBCPP cells with E-30 were obtained when the cells were challenged apically with a MOI (multiplicity of infection) of 20 [ 28 ]. Now, we further analyzed several parameters, such as the transepithelial resistance, the cytotoxic effect of E-30, the number of viral particles per HIBCPP cells, and the percentage of infected HIBCPP cells ( Supplemental Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study of our laboratory on E-30 infection of the HIBCPP with MOI 20 revealed a strong impact of the virus at the RNA level [ 28 ]. We compared the differentially expressed genes after E-30 infection in HIBCPPP with the new proteomic results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations